Strategi Komunikasi melalui Pembelajaran Jurnalistik untuk Mengembangkan Kreativitas Menulis Santri di Pondok Pesantren Sinarsari - Regtria Cahaya Maulida; Haryadi Mujianto; Detya Wiryany (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research is based on the low level of journalism learning in the Sinarsari Islamic Boarding School environment, resulting in a lack of interest in students' writing skills in the Youth Scientific Work extracurricular activity. Based on the data, it shows that the level of students' interest in writing creativity has not reached its maximum level from year to year, one of which is due to the low level of journalism learning and the tight schedule of students' activities. This study aims to examine how the impact of the quality of journalism learning can affect students' writing creativity during the Youth Scientific Work extracurricular activity process. In this study, a qualitative analysis method approach was applied by collecting data through interviews, observation, and documentation. This research study is more about researchers explaining the development of students' writing creativity through the Youth Scientific Work extracurricular activity. Respondents in this study were students of the Sinarsari Islamic Boarding School and supervising teachers who actively participated in the Youth Scientific Work extracurricular activity. Humanistic theory is used as an analytical framework to see how journalism learning can develop students' creativity. With five main dimensions, namely self-actualization, self-concept, learning, organism experience and autonomy, independence and responsibility. The results of this study indicate that journalism learning significantly influences the development of students' creativity. The researchers recommend more in-depth guidance regarding journalism learning to foster more imaginative characters and open up opportunities for self-development.